PENDAMPINGAN PENGELOLAAN CHANNEL YOUTUBE UNTUK BRANDING KB DAN TK TIARA NUSA KLATEN - Sulistyowati, Istri; Setyawan, Doni; Yusuf, Mahmud; Retnowati, Niken; Suradi, Agustinus (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
The Community Service Activity entitled "Assistance in the Management of Youtube Channels for Branding KB and TK Tiara Nusa Klaten aims to provide information, as a means of communication and documentation as well as to build school branding because in the ever-evolving landscape of social media platforms, YouTube stands out as a dynamic force that continues to expand its reach globally. The methods used in this activity are observation, communication, training, and assistance in creating digital content and YouTube accounts. The result of this service activity is a variety of digital content, and a YouTube account contains several digital pieces of and a YouTube account contained several digital pieces of and a YouTube account that contains has contained several digital content that will be used to build the school's branding.